Peningkatan Kemampuan Komunikasi Matematis Melalui Strategi Group Investigation ( Ptk Pada Siswa Kelas Viii B Semester Genap Smp Al Islam Tahun 2015/2016) - Rahmawatiningrum, Alfiyatu, Idris Harta M.A, Ph.D (2016)
The aim of this research is to increase student's mathematical communication skill through the Group Investigation of strategy in class VIII B second semester SMP Al Islam Kartasura. This research is a classroom action research conducted collaboratively between researchers and teachers of mathematics. The Recipients action is class VIII B of SMP Al Islam Kartasura as many as 30 students and the perpetrator is a teacher of mathematics. Data collection techniques in this study using observation, testing, field notes, and documentation. Data analysis techniques used in this study is the reduction, data presentation, and conclusion. The result of this research is the increasing ability of students' mathematical communication skill, it can be seen from a loyal following indicators: (1) Students who can convey mathematical ideas orally prior to the action as much as 7 students (23.33%), after measures were 21 students (70% ); (2) Students who can convey mathematical ideas in writing before action by 5 (16.67%), after action by 25 students (83.33%); (3) Students who can convey the idea of mathematical images before the procedure as much as 4 students (13.33%), after action by 17 students (56.67%); (4) Students who can convey mathematical ideas to explain the concept of prior actions as much as 7 students (23.33%), after measures were 24 students (80%)